Single cell-level detection and quantitation of leaky protein expression from any strongly regulated bacterial system - Arora, Kanika; Guptasarma, P. (Science Direct, 2015)
Extremely low levels of "leaky" expression of genes in bacterial protein expression systems can severely curtail cell viability when expressed proteins are toxic. A general method for sensitive detection of such expression is lacking. Here, we present a method based on microscopic visualization of a fluorescent "reporter" protein (RFP-HU-A) constructed by fusing red fluorescent protein (RFP) to the N-terminus of a nucleoid-associated, histone-like DNA-binding protein, HU-A. Localization of RFP-HU-A within nucleoids facilitates detection, quantitation, and characterization of leaky expression at the single-cell level.
Only IISERM authors are available in the record.
Keywords: cell-level; quantitation; protein; bacterial